KAZAKH BUSINESS DISCOURSE: PECULIARITIES OF KAZAKH BUSINESS MEETINGS - Karibayeva, Buadat; Kunanbayeva, Salima S (PEOPLE: International Journal of Social Sciences, 2016)
The Republic of Kazakhstan is a young country, which is actively developing since its independence in 1991. The way of doing business by entrepreneurs has evolved in twenty five years with some features of Soviet Union, renascence of Kazakh cultural values and western influence, so has the way of communication in the Kazakh business. Meeting in Kazakh business is more of a tool to minute decisions made prior the formal communication in order resolve business challenges and conduct day-to-day activities. Therefore, informal meetings are playing the significant role in pure Kazakh business culture. This is mainly because of the cultural perception and preferences, as well as the language to communicate it. This paper depicts the analysis of academic researches, which discusses factors relevant to Kazakh business discourse. It argues that factors of cultural perception and preferences along with business language context affect the Kazakh business meetings. It highlights the peculiarities of Kazakh business meetings, which has altered during the years of independence. Although, meetings in Kazakh business normally reflect decisions only, Kazakh perception of the purpose of the meeting is changing. The meetings, especially with the international involvement, reflect discussions as well. Decisions in such meetings are made during the meeting as a result of discussion. The importance of perception by Kazakh culture and language context is also discussed in this paper.